Transparency in Hierarchies - Christian Hofmann; Raffi J. Indjejikian (Journal of Accounting Research, 2023)
We use an agency model to address the benefits and costs of transparency in a hierarchical organization in which the principal employs a manager entrusted with contracting authority and several workers, all under conditions of moral hazard. We define the principal's transparency choices as a decision to allow workers to observe their coworkers' performances (observability) and as an investment in monitoring worker performance (precision). We find that whereas precision alleviates agency conflicts as expected, observability can exacerbate agency conflicts, especially if the manager's interests are misaligned sufficiently with those of the principal. Our results suggest several testable hypotheses including predictions that opaque performance measurement practices are well suited for small organizational units at lower hierarchical ranks, and in settings where the sensitivity-precision of the available measures is low, workers' performances are correlated positively, and managerial productivity is modest.
Keywords: 650; hierarchy; incentives; multiagent contracting; relative performance evaluation; performance measure precision